Progress in Botany Vol. 76 - Lüttge, Ulrich; Beyschlag, Wolfram; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
With one volume each year, this series keeps scientists and advanced students informed of the latest developments and results in all areas of the plant sciences. The present volume includes reviews on physiology, ecology and vegetation science.
Fifty-five years of research on photosynthesis, chloroplasts and stress physiology of plants: 1958 – 2013 -- Alfred Russel Wallace: Self-Educated Genius and Polymath -- The role of plasma membrane H+-ATPase in salinity stress of plants -- Selenium in Plants -- Interplay of water and nutrient transport: A whole-plant perspective -- Electrical signaling in plants -- Adaptations of chloroplastic metabolism in halophytic plants -- CAM-like traits in C3 plants: biochemistry and stomatal behavior -- Stability as a Phenomenon Emergent from Plasticity – Complexity – Diversity in Eco-Physiology -- The proposed anti-herbivory roles of white leaf variegation -- Solar UV radiation and plant litter decomposition -- Interspecific competition in Arabidopsis thaliana - a short review on how a knowledge gap is starting to close -- Growth limitation and C-relations in trees under environmental stress -- Consequences of changing precipitation patterns for productivity and diversity in grassland ecosystems -- Do plant responses to tropospheric ozone translate into ecosystem effects?.
Keywords: Plant science; Botany; Plant Sciences